2018
DOI: 10.1097/jsm.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Athletes Disability Index Questionnaire

Abstract: The ADI is a reliable and valid instrument for assessing disability in athletes with LBP. Compared with the available LBP disability questionnaires used in the general population, ADI can more precisely stratify the disability levels of athletes due to LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 26 publications
1
22
0
4
Order By: Relevance
“…The reason could be due to a lack of an appropriate assessment tool in athletes since the questionnaires used for LBP disability in the general population are not applicable for the athletes as they likely exhibit a ceiling effect. In an earlier observation, our colleagues confirmed the validity and reliability of the Persian version of the Athletes Disability Index Questionnaire (ADI) which has been developed specifically for athletes ( Noormohammadpour et al, 2018 ). Athletes are an underrepresented group in many neck pain and LBP studies, and little has been published regarding the prevalence of neck pain and LBP in athletes especially in Olympiads.…”
Section: Introductionmentioning
confidence: 64%
“…The reason could be due to a lack of an appropriate assessment tool in athletes since the questionnaires used for LBP disability in the general population are not applicable for the athletes as they likely exhibit a ceiling effect. In an earlier observation, our colleagues confirmed the validity and reliability of the Persian version of the Athletes Disability Index Questionnaire (ADI) which has been developed specifically for athletes ( Noormohammadpour et al, 2018 ). Athletes are an underrepresented group in many neck pain and LBP studies, and little has been published regarding the prevalence of neck pain and LBP in athletes especially in Olympiads.…”
Section: Introductionmentioning
confidence: 64%
“…For the PKE test, the angle between a horizontal reference line and the shin was noted, where higher values indicate larger flexibility (90° represent a full extended knee). A questionnaire includes items of the Athletes Disability Index Questionnaire and German Pain Questionnaire to obtain the presence and characteristics of pain and personal sport history.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, back pain affects the formation of structures in the lumbar region [13,14] and causes knee [15] and shoulder [16] pain during high impact sports [17,18]. Thus, it has been studied for several sports such as rowing, rugby, football, fighting, and gymnastics [19][20][21][22][23][24]. In the literature, systematic reviews have concluded that age, advanced and late puberty, family history of back pain, asthma, headaches, abdominal pain, depression, and anxiety are potential risk factors that trigger back pain [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several tools for assessing back pain in athletes have been developed or adapted [20]. However, the definition of "athlete" varies [42][43][44], which can influence the criteria for selecting participants for studies.…”
Section: Introductionmentioning
confidence: 99%